Suppression of asparaginyl endopeptidase attenuates breast cancer-induced bone pain through inhibition of neurotrophin receptors - Yao, Peng (Mol Pain, 2017)
OBJECTIVE: Cancer-induced bone pain is a common clinical problem in breast cancer patients with bone metastasis. However, the mechanisms driving cancer-induced bone pain are poorly known. Recent studies show that a novel protease, asparaginyl endopeptidase (AEP) plays crucial roles in breast cancer metastasis and progression. We aim to determine the functions and targeted suppress of AEP in a mouse model of breast cancer-induced bone pain. METHODS: Breast cancer cells with AEP knocked-down or overexpression were constructed and implanted into the intramedullary space of the femur to induce pain-like behavior in mice. AEP-specific inhibitors or purified AEP proteins were further used in animal model. The histological characters of femur and pain ethological changes were measured. The expressions of AEP and neurotrophin receptors (p75NTR and TrkA) in dorsal root ganglion and spinal cord were examined. RESULTS: Femur radiographs and histological analysis revealed that cells with AEP knocked-down reduced bone destruction and pain behaviors. However, cells with AEP overexpression elevated bone damage and pain behaviors. Further, Western blot results found that the expressions of p75NTR and TrkA in dorsal root ganglions and spinal cords were reduced in mice inoculated with AEP knocked-down cells. Targeted suppression of AEP with specific small compounds significantly reduced the bone pain while purified recombinant AEP proteins increased bone pain. CONCLUSIONS: AEP aggravate the development of breast cancer bone metastasis and bone pain by increasing the expression of neurotrophin receptors. AEP might be an effective target for treatment of breast cancerinduced bone pain.